Exploring the structural basis and functional immunodynamics of immunoglobulin M in host defense against fungal pathogens - Pruksaphon, Kritsada; Khamto, Nopawit; Amsri, Artid; Wagatsuma, Monsicha; Nosanchuk, Joshua D.; Higuchi, Yujiro; Youngchim, Sirida (Frontiers in Immunology, 2025)
The rising prevalence of life-threatening fungal infections, particularly in immunocompromised individuals, necessitates a deeper understanding of all facets of the host immune response. While much focus has been placed on cellular immunity, the contribution of Immunoglobulin M (IgM), the first antibody produced during an immune response, remains a relatively underexplored area in the context of systemic mycoses. This comprehensive survey explores the role of IgM in antifungal immunity, with a focus on life-threatening fungal infections. As the earliest antibody isotype, IgM achieves remarkable binding diversity through germline-encoded V(D)J recombination without requiring somatic hypermutation. Its multimeric structure enables high-avidity recognition of fungal cell wall components, facilitating binding despite antigenic variability of opportunistic pathogens. While conserved fungal polysaccharides activate host pattern recognition receptors, pathogenic fungi have evolved exopolysaccharides that shield immunogenic motifs from detection. IgM recognizes these complex carbohydrate epitopes and triggers complement activation, enhancing opsonophagocytic clearance. Evolutionarily conserved across vertebrates, IgM provides critical broad-spectrum protection through germline-encoded diversity. Despite these advantages, IgM’s therapeutic potential in systemic mycoses remains underexplored, particularly in immunocompromised individuals. This review presents evidence on the molecular basis and immunological functions of IgM, highlighting its contributions to immunity against pathogenic fungi and identifying promising avenues for translational research across various clinically relevant fungal species.